Practice Patterns for Management of Pediatric Femur Fractures in Low- and Middle-Income Countries. Issue 5 (May 2020) - Curran, Patrick F.; Albright, Patrick; Ibrahim, John M.; Ali, Syed H.; Shearer, David W.; Sabatini, Coleen S.
Abstract : Background: Femoral shaft fractures in children are common in low and middle income countries. In high-income countries, patient age, fracture pattern, associated injuries, child/family socioeconomic status, and surgeon preference dictate fracture management. There is limited literature on treatment patterns for pediatric femur fractures in resource-limited settings. This study surveys surgeons from low (LIC), lower-middle (LMIC), and upper-middle income (UMIC) countries regarding treatment patterns for pediatric femur fractures. Methods: Surgeons completed an electronic survey reporting surgeon demographics and treatment preference for pediatric femur fractures. Treatment preferences and indications for treatment were separated into 4 groups: infant (0 to 6 mo); toddler (7 mo to 4 y); child (5 to 12 y); adolescent (12 to 17 y). The survey was available in English, Spanish, and French. Analysis was completed with t test and χ 2 test for continuous and categorical variables, respectively, and weighted Pearson correlation ( P <0.05). Results: Survey respondents consisted of 413 surgeons from 83 countries (20 LIC, 33 LMIC, 30 UMIC). The majority of respondents were fellowship trained (83%) most commonly in pediatrics (26%) and trauma (43%). Most treated >10 pediatric femur fractures per year (68%). Respondents reported treating infant femur fractures nonoperatively using Pavlik harness (19%), spica cast (60%), or traction with delayed spica cast (14%). Decreasing socioeconomic status was associated with higher nonoperative treatment rate in toddlers, children, and adolescents. Respondents commonly utilize bed rest and traction for child femur fractures in LICs (63%) and LMICs (65%) compared with UMICs (35%) (UMIC vs. LMIC P <0.001; UMIC vs. LIC P <0.001). Surgeries in children more commonly involve open reduction with internal fixation (UMIC 19%, LMIC 33%, LIC 40%; P <0.05 between UMIC-LMIC and UMIC-LIC). Conclusion: This is one of the largest surveys describing treatment patterns for pediatric femur fractures in low and middle income countries. Differences are evident including lower operative treatment rate in younger children and lower intramedullary fixation rates in older children. Future studies should investigate the value of treatment options in resource-limited settings. Level of Evidence: Level II—prospective comparative study.